2013
DOI: 10.1164/rccm.201210-1886oc
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-induced Changes in Gene Expression of Airway Smooth Muscle in Patients with Asthma

Abstract: Oral prednisolone changes the transcriptomic profile of the ASM layer in asthma. This indicates that in parallel to antiinflammatory properties, glucocorticoids also exert effects on gene expression of ASM, which is correlated with improved airway function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…Four of the genes (RPTOR, VANGL1, FAM129A, and LEPREL1) were associated with AHR. In a second study by this group, they were able to show that asthmatic ASM from patients treated with glucocorticoids had changes in the expression of genes related to cellular growth, proliferation, and development (Yick et al 2013). Interestingly, prednisone treatment was able to reverse the down-regulation of FAM129A, which was associated with AHR in the first study.…”
Section: Proteins Unrelated To Contractile Functionmentioning
confidence: 91%
See 1 more Smart Citation
“…Four of the genes (RPTOR, VANGL1, FAM129A, and LEPREL1) were associated with AHR. In a second study by this group, they were able to show that asthmatic ASM from patients treated with glucocorticoids had changes in the expression of genes related to cellular growth, proliferation, and development (Yick et al 2013). Interestingly, prednisone treatment was able to reverse the down-regulation of FAM129A, which was associated with AHR in the first study.…”
Section: Proteins Unrelated To Contractile Functionmentioning
confidence: 91%
“…Two recent studies using RNA-seq have identified changes in the expression of genes not directly related to ASM contractile function in asthmatic versus non-asthmatic tissue (Yick et al 2013(Yick et al , 2014. In their first paper, they micro-dissected ASM from asthmatics and found 174 genes differentially expressed when compared with the controls.…”
Section: Proteins Unrelated To Contractile Functionmentioning
confidence: 99%
“…Part of it is mediated by direct and indirect genomic (i.e. transcriptional) effects (Yick et al 2013), and part of it is exerted by a rapid non-genomic effect (Sun et al 2006). Indeed, acute or prolonged exposure to glucocorticoids reduces the contraction elicited by spasmogens and potentiates the relaxing response to b 2 -adrenergic receptor activation.…”
Section: Adrenalsmentioning
confidence: 99%
“…Three studies were published in the Journal in 2013 that identified new factors that may affect airway smooth muscle contraction and relaxation (55)(56)(57). Two of the studies applied multiple modalities to mouse, guinea pig, and human tissues and identified transmembrane protein 16A, a calcium-activated chloride channel, and Toll-like receptor 7, respectively, as factors that modify the response of airway smooth muscle to contractile agents (56,57).…”
Section: Pathways That Affect Smooth Musclementioning
confidence: 99%
“…Two of the studies applied multiple modalities to mouse, guinea pig, and human tissues and identified transmembrane protein 16A, a calcium-activated chloride channel, and Toll-like receptor 7, respectively, as factors that modify the response of airway smooth muscle to contractile agents (56,57). The third study combined laser capture microdissection of human airway biopsies and RNA sequencing to identify two genes (FAM129A and SYNPO2) that were significantly changed in expression with corticosteroids in asthma and which correlated with degree of airway hyper-responsiveness (55). Although technologically ambitious, that study was relatively small and did not pursue complementary modalities to assess the potential role of these genes.…”
Section: Pathways That Affect Smooth Musclementioning
confidence: 99%